Cofiniteness with respect to Extension of Serre Subcategories at Small Dimensions - Reza Sazeedeh (Journal of Mathematics)
Let A denote a commutative Noetherian ring, a be an ideal of A, X be an arbitrary dense subcategory of A-modules, and N be the full subcategory of finite A-modules. In this paper, we study N⋆X-c-cofinite modules with respect to the extension subcategory N⋆X when dim A/c≤2. We also study c-cofiniteness with respect to a new dimension.